2015
DOI: 10.4012/dmj.2014-319
|View full text |Cite
|
Sign up to set email alerts
|

Improving shear bond strength between feldspathic porcelain and zirconia substructure with lithium disilicate glass-ceramic liner

Abstract: This study investigated the shear bond strength (SBS) between veneering porcelain and zirconia substructure using lithium disilicate glass-ceramic as a liner. The mineral phases and microstructures of lithium disilicate glass-ceramic at temperature range of 800-900°C were preliminarily investigated. SBSs of porcelain-veneered zirconia specimens with and without lithium disilicate glassceramic liner fired at the same temperature were determined. Results showed that SBSs of veneering porcelain and zirconia with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…These results were concomitant with previous studies (11,13,24,29,30) which found that the application of liner on sintered zirconia increase the bond strength with its layered veneering ceramics. They found that the liner application increase the wettability which affect the bond strength of the veneered restorations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results were concomitant with previous studies (11,13,24,29,30) which found that the application of liner on sintered zirconia increase the bond strength with its layered veneering ceramics. They found that the liner application increase the wettability which affect the bond strength of the veneered restorations.…”
Section: Discussionsupporting
confidence: 91%
“…The color of underlying zirconia core can be masked through liner application which in turn can be used for adjusting the porcelain color. There are different reports about the effect of liner on the zirconia veneer bond strength and these reports are differing, however, some was found that the bond strength was increased (11,12) , while others founding a decrease (13) .…”
Section: Introductionmentioning
confidence: 99%
“…Wattanasirmkit et al [ 2 ] concluded that the highest SBS of vitali850 was a result of lithium disilicate glass–ceramic forming good adhesion to zirconia and the two veneering porcelain layers.…”
Section: Discussionmentioning
confidence: 99%
“…Lithium disilicate with coefficient of thermal expansion (CTE [25°C –800°C]: ~9.3–9.9 × 10 − 6 K −1 ) is a type of glass ceramic which offers thermal shock resistance, thus leading to a more stable CTE even after multiple firings. [ 2 ] The SBS indicates interceramic bond between zirconia core and veneering ceramics. [ 3 ] Strong discrepancies in CTE between veneering porcelains and zirconia significantly affect their bond strength.…”
Section: Introductionmentioning
confidence: 99%
“…[14] The average result of 27 MPa of bonding strength between porcelain and zirconia in this study corroborated the results found in other works, regardless of the test applied. [1,[11][12][13][16][17][18][19][20][21][22][23][24][25] Zirconia surface can be treated with aluminum oxide, diamond drills, or silica coating blasting. Some authors [13] reported that surface treatment with aluminum oxide blasting results in roughness and increases zirconia's surface energy.…”
Section: Discussionmentioning
confidence: 99%